A full three‐dimensional fracture propagation model for supercritical carbon dioxide fracturing. Issue 8 (10th June 2020) - He, Yuting; Yang, Zhaozhong; Jiang, Yanfang; Li, Xiaogang; Zhang, Yongqing; Song, Rui
Abstract: Supercritical carbon dioxide fracturing is an environmentally friendly anhydrous method. To study the propagation process during supercritical carbon dioxide fracturing, a full three‐dimensional model, coupled rock deformation, fluid transport, heat conduction, dynamic changes of carbon dioxide physical parameters, to investigate the process of fracture propagation during supercritical carbon dioxide fracturing, is established by the three‐dimensional boundary element method, the finite volume method, and finite difference method. And to solve the multiple physics coupling problems, a fully implicit solution and Newton‐Raphson iteration method are used. On the basis of this model established in this paper, the influential factors of supercritical carbon dioxide fracturing are analyzed. The results show that both of the reservoir temperature and the original in situ stress are important for carbon dioxide fracturing; The higher the reservoir temperature and the lower the initial in situ stress is, the longer and wider the fracture will be. The temperature of carbon dioxide at bottom is of no significance to the fracture length, fracture width, and the bottom hole pressure. A growing injection rate will lead to the increase of the fracture length and fracture width. This study would provide a reference for the fluid phase control of supercritical carbon dioxide fracturing technology. Abstract : Supercritical carbon dioxide fracturing is an environmentally friendly anhydrous method. In order to study the propagation process during supercritical carbon dioxide fracturing, a full three‐dimensional model coupled with thermal‐hydro‐mechanical process of supercritical carbon dioxide fracturing is established by the three‐dimensional boundary element method and the finite volume method. On the basis of this model established in this paper, the influential factors of supercritical carbon dioxide fracturing are analyzed.